Między gramatyką a słownikiem – słowotwórstwo w perspektywie glottodydaktycznej - Anna Seretny; Wiesław Stefańczyk (Postscriptum Polonistyczne)
Knowledge of word formation is an important element of the grammatical competencies of native speakers. Studying forms and functions of derivates and practising using them is also extremely important for foreigners studying Polish. This article contributes to the discussion about the position and function of word formation in the process of education. The authors claim that a specific system of derivation must determine the way in which it is taught. Critical analysis of solutions that have been used in glottodidactics, suggest a new approach, which would place the didactics of word formation ‘between’ grammar and vocabulary.